VARIABEL YANG MEMPENGARUHI TAX AVOIDANCE PADA PERUSAHAAN MANUFAKTUR - NATASHA THALIA WIJAYA; MUNGNIYATI (E-Jurnal Manajemen Trisakti School of Management (TSM), 2026)
The purpose of this study is to provide empirical evidence on the influence of profitability, leverage, capital intensity, firm size, firm age, sales growth, and transfer pricing on tax avoidance. The study focuses on manufacture companies listed on the Indonesia Stock Exchange (IDX) during the period of 2022-2024. Purposive sampling was employed, involving 126 companies or 378 data points. The research utilized multiple regression analysis to analyze the data. The findings indicate that sales growth have an influence on tax avoidance, whereas profitability, leverage, capital intensity, firm size, firm age, and transfer pricing do not affect tax avoidance.